Mechanistic diversity and regulation of Type II fatty acid synthesis. (November 2002) - Marrakchi, H.; Zhang, Y.-M.; Rock, C. O.
Abstract : Fatty acid biosynthesis is catalysed in most bacteria by a group of highly conserved proteins known as the Type II fatty acid synthase (FAS) system. The Type II system organization is distinct from its mammalian counterpart and offers several unique sites for selective inhibition by antibacterial agents. There has been remarkable progress in the understanding of the genetics, biochemistry and regulation of Type II FASs. One important advance is the discovery of the interaction between the fatty acid degradation regulator, FadR, and the fatty acid biosynthesis regulator, FabR, in the transcriptional control of unsaturated fatty acid synthesis in Escherichia coli. The availability of genomic sequences and high-resolution protein crystal structures has expanded our understanding of Type II FASs beyond the E. coli model system to a number of pathogens. The molecular diversity among the pathway enzymes is illustrated by the discovery of a new type of enoyl-reductase in Streptococcus pneumoniae [enoyl-acyl carrier protein (ACP) reductase II, FabK], the presence of two enoyl-reductases in Bacillus subtilis (enoyl-ACP reductases I and III, FabI and FabL), and the use of a new mechanism for unsaturated fatty acid formation in S. pneumoniae (trans-2-cis -3-enoyl-ACP isomerase, FabM). The solution structure of ACP from Mycobacterium tuberculosis revealed features common to all ACPs, but its extended C-terminal domain may reflect a specific interaction with very-long-chain intermediates.